Exploring the relationship between health literacy and chronic diseases among middle-aged and older adults: evidence from Zhejiang, China - Li, Shuqi; Yao, Dingming; Hu, Xiujing; Chen, Heni; Yan, Xiaotong; Xu, Yue; Zhang, Xuehai (Frontiers in Public Health, 2025)
BackgroundChronic diseases have emerged as a significant public health challenge owing to the escalating global demographic shift toward an aging population. Middle-aged and older individuals are particularly vulnerable to chronic illnesses owing to physiological and socioeconomic changes. By leveraging health literacy data from the Zhejiang Province, this study aimed to elucidate the correlation between health literacy levels and the prevalence of chronic diseases in this demographic cohort.MethodsIn this cross-sectional study, a stratified multistage whole-cluster random sampling method was used to select 12,116 permanent residents aged 45–69 years from 30 monitoring sites in Zhejiang Province from June to November 2023, using the National Health Literacy Monitoring Questionnaire for the Population. Multivariate regression analysis was employed to unravel the correlation between proficiency in health education and the prevention of chronic illnesses.ResultsSex, age, income, education, self-assessed health status, and smoking status emerged as significant predictors across the different models. Notably, self-assessed health and smoking statuses were identified as confounders that significantly affected the association between health literacy and chronic diseases. Furthermore, this study explored the influence of independent variables on specific chronic diseases, such as hypertension and cerebrovascular disease, with consistent patterns observed across models.ConclusionHealth literacy is instrumental in thwarting chronic diseases among middle-aged and older individuals. Those with higher levels of health literacy are less likely to suffer from chronic diseases, and high health literacy is a protective factor against hypertension and cerebrovascular disease.